Lignans from the seed shells of Cerasus humilis (Bge.)Sok and their bioactivities - Sun, Y.; Zhou, Y.; Dong, S.; Tang, X.; Ren, Y.; Liu, X.; Zhang, G.
The exploration of Cerasus humilis (Bge.)Sok seed shells yielded the identification of six previously uncharacterized compounds, in addition to twelve known compounds. Structure elucidation of these compounds relied on spectroscopic data analysis, and their absolute configurations were established by comparing calculated and experimental electronic circular dichroic (ECD)spectra, supplemented by interpretation of optical rotation data. Notably, none of these compounds exhibited cytotoxicity against HepG2 and A549 cell lines. Remarkably, a majority of the compounds displayed potent antioxidant activity.
Keywords: ANTIOXIDANT ACTIVITY; CERASUS HUMILIS (BGE.)SOK; LIGNANS; ROSACEAE; SEED SHELLS